Widger's Quotations from the Project Gutenberg Editions of the Works of Guy de Maupassant - Maupassant, Guy de, 1850-1893; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2003)
"Widger's Quotations from the Project Gutenberg Editions of the Works of Guy de$1! =(B", edited by David Widger, is a collection of selected quotations drawn from the complete short stories written by the renowned French author Guy de Maupassant. This compilation is likely created during the early 21st century and serves as a reference resource, highlighting the thematic richness and stylistic nuances of Maupassant's narratives. The main focus of the book is to provide readers with memorable passages that encapsulate the essence of Maupassant$1 (Bs storytelling. The content of this book consists of a variety of quotations that reflect the diverse themes and characters present in Maupassant's extensive collection of short stories. These excerpts capture the complex emotions explored in his tales, such as love, despair, societal critique, and the human condition. By featuring both small passages and one-liners, Widger's collection enables readers to appreciate the wit and depth of Maupassant$1 (Bs writing, fostering a greater understanding of the author's literary contributions and inspiring readers to seek out the full stories for a deeper exploration of the themes presented. (This is an automatically generated summary.)s
Release date is 2003-01-01
This etext was produced by David Widger
Keywords: Quotations